(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
The present study was done to evaluate a multiplex PCR based method for simultaneous detection of Neisseria meningitidis, Streptococcus pneumoniae and Haemophilus influenzae in CSF. A cross sectional study was carried out with 140 children (2 months to 12 years of age) with clinical suspicion of acute meningitis during July 2010 to June 2011. Three species-specific primers were used along with universal primers of bacterial gene 16S rRNA, in a two-stage PCR assay for diagnosis of acute bacterial meningitis.Among 140 patients, 42 (30%) cases were diagnosed as bacterial meningitis and other 98 (70%) as viral meningitis by clinical and cytobiochemical criteria. Out of 42 bacterial meningitis cases, 9 (21.43%) were positive by Gram stain.These 9 cases were also positive by bacterial culture and PCR. Again, 15 (35.71%) were positive by bacterial culture which were also PCR positive. In 27 cases (out of 42), the etiologic diagnosis was not possible using routine bacteriological methods; in 11 of these patients, the etiologic agents were identified by PCR. In addition, PCR recognized 5 more cases whose etiologic diagnosis was not possible, as they were identified by universal primer of 16S rRNA. Hence, among 31 (73.81%) PCR positive cases, 12 (38.71%) were S. pneumoniae, 10 (32.26%) were H. influenzae, 4 (12.9%) were N. meningitidis and 5 (16.13%) were other bacteria.Among the antibiotic users, bacterial meningitis case detection by PCR was higher (65.52%) than that of culture (10.34%) and Gram staining (6.90%). The overall sensitivity and specificity of PCR assay was 100% and 66% respectively when bacterial culture was considered as gold standard. PCR can be used as a valuable supplementary diagnostic technique in routine clinical practice for diagnosis of acute bacterial meningitis in hospital setting. Bangladesh J Med Microbiol 2017; 11 (2): 9-16